Comunicación audiovisual en el proceso de enseñanza y aprendizaje con los estudiantes de la Escuela Quintiliano Sánchez Rendón del año 2022 - Martínez Loor, Jessica Johana (2022)
The use of the visual medium constitutes the didactic resource that can be implemented thanks to technology in the classroom and outside of it, thus being able to offer a competitive education according to the needs of the students of the school. The objective of the research was to analyze audiovisual communication in the teaching and learning process in the students of the Quintiliano Sánchez Rendón School. The methodology used corresponded to a qualitative, bibliographic, interview and observation approach. The population is made up of the total number of students at the Quintiliano Sánchez Rendón School. The sample consisted of students from two classrooms. The main conclusion was that the use of audiovisual media for teaching and learning in which it significantly influences the academic performance of the students of the Quintiliano Sánchez Rendón School.